2005
DOI: 10.1007/s10350-004-0902-7
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcome of Pouch-Vaginal Fistulas Following Restorative Proctocolectomy

Abstract: Pouch-vaginal fistulas can persist and recur indefinitely, even after repeated repairs. Repair in those patients with Crohn's disease uniformly failed within five years from primary repair. Patients with recurrent pouch-vaginal fistulas and ulcerative colitis should be offered salvage surgery because successful closure following initial failure occurs in approximately 50 percent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 24 publications
0
45
1
6
Order By: Relevance
“…Ileal pouch fistulas are an uncommon and devastating complication for patients, and a challenging problem for surgeons. Several studies have assessed ileal pouch-vaginal fistula formation after RPC with IAA [16][17][18][19][20], but little has been published on overall perianal fistula formation after RPC.…”
Section: Discussionmentioning
confidence: 99%
“…Ileal pouch fistulas are an uncommon and devastating complication for patients, and a challenging problem for surgeons. Several studies have assessed ileal pouch-vaginal fistula formation after RPC with IAA [16][17][18][19][20], but little has been published on overall perianal fistula formation after RPC.…”
Section: Discussionmentioning
confidence: 99%
“…Heriot AG et al [19] reported recurrence in 27 of 45 (60 %) patients who underwent primary repair. In our study, pouchvaginal fistulae developed in three patients after restorative proctocolectomy and were successfully repaired in two.…”
Section: Discussionmentioning
confidence: 99%
“…24,34 Local procedures are suitable for PVF originating below the IPAA, and include transanal or transvaginal advancement full-thickness flap repair. Primary closure rate is below 60%, 34,35 but transvaginal repair allows direct access to the fistula, avoiding sphincter damage.…”
Section: Septic Complicationsmentioning
confidence: 99%
“…33 The approach depends on the site of PVF. 34 Abdominal repairs are needed for PVF originating above the IPAA, and mainly consist of pouch revision or redo, with primary repair of the vaginal defect, resection of the potentially retained rectum, mucosectomy, and advancement of the IPAA below the level of the fistula. 34 Primary healing is reported in 67-80% of patients.…”
Section: Septic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation